Network pharmacology and experimental verification of the mechanism of licochalcone A against Staphylococcus aureus pneumonia - Shen, Fengge; Zhang, Yinghua; Li, Chunjie; Yang, Hongyan; Yuan, Peng (Frontiers in Microbiology, 2024)
Staphylococcus aureus (S. aureus) strains cause the majority of pneumonia cases and are resistant to various antibiotics. Given this background, it is very important to discover novel host-targeted therapies. Licochalcone A (LAA), a natural plant product, has various biological activities, but its primary targets in S. aureus pneumonia remain unclear. Therefore, the purpose of this study was to identify its molecular target against S. aureus pneumonia. Network pharmacology analysis, histological assessment, enzyme-linked immunosorbent assays, and western blotting were used to confirm the pharmacological effects. Network pharmacology revealed 33 potential targets of LAA and S. aureus pneumonia. Enrichment analysis revealed that these potential genes were enriched in the Toll-like receptor and NOD-like receptor signaling pathways. The results were further verified by experiments in which LAA alleviated histopathological changes, inflammatory infiltrating cells and inflammatory cytokines (TNF, IL-6 and IL-1β) in the serum and bronchoalveolar lavage fluid in vivo. Moreover, LAA treatment effectively reduced the expression levels of NF-κB, p-JNK, p-p38, NLRP3, ASC, caspase 1, IL-1β and IL-18 in lung tissue. The in vitro experimental results were consistent with the in vivo results. Thus, our findings demonstrated that LAA exerts anti-infective effects on S. aureus-induced lung injury via suppression of the Toll-like receptor and NOD-like receptor signaling pathways, which provides a theoretical basis for understanding the function of LAA against S. aureus pneumonia and implies its potential clinical application.